2021
DOI: 10.3390/biom11081172
|View full text |Cite
|
Sign up to set email alerts
|

Routes for Potassium Ions across Mitochondrial Membranes: A Biophysical Point of View with Special Focus on the ATP-Sensitive K+ Channel

Abstract: Potassium ions can cross both the outer and inner mitochondrial membranes by means of multiple routes. A few potassium-permeable ion channels exist in the outer membrane, while in the inner membrane, a multitude of different potassium-selective and potassium-permeable channels mediate K+ uptake into energized mitochondria. In contrast, potassium is exported from the matrix thanks to an H+/K+ exchanger whose molecular identity is still debated. Among the K+ channels of the inner mitochondrial membrane, the most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 129 publications
(155 reference statements)
0
19
0
Order By: Relevance
“…Later, the same type of channel was identified in other tissues, such as the heart [ 8 , 9 , 10 ], brain [ 11 , 12 , 13 ], skeletal muscle [ 14 ], human T-lymphocytes [ 15 ], and skin fibroblasts [ 16 ]. Electrophysiological experiments revealed that the conductance of the channel is usually close to 100 pS [ 11 , 17 , 18 , 19 ]; however, channels with lower conductance, close to 10 pS, have also been reported [ 7 , 8 ]. These differences in reported conductance may result from the various experimental conditions.…”
Section: Modulators Of Mitochondrial Atp-sensitive Potassium Channelsmentioning
confidence: 99%
“…Later, the same type of channel was identified in other tissues, such as the heart [ 8 , 9 , 10 ], brain [ 11 , 12 , 13 ], skeletal muscle [ 14 ], human T-lymphocytes [ 15 ], and skin fibroblasts [ 16 ]. Electrophysiological experiments revealed that the conductance of the channel is usually close to 100 pS [ 11 , 17 , 18 , 19 ]; however, channels with lower conductance, close to 10 pS, have also been reported [ 7 , 8 ]. These differences in reported conductance may result from the various experimental conditions.…”
Section: Modulators Of Mitochondrial Atp-sensitive Potassium Channelsmentioning
confidence: 99%
“…The triggering of long-term oscillations in ion fluxes required an increase in the permeability of the mitochondrial membrane to potassium ions. This can be explained by the fact that, under the resting-state conditions, the rate of the transport of K + ions across the mitochondrial membrane is one order of magnitude lower than that of Ca 2+ or Sr 2+ [ 36 , 37 , 41 ]. Therefore, potassium influx can limit the next oscillation wave.…”
Section: Discussionmentioning
confidence: 99%
“…Chance, R. Packer, and others [ 6 , 13 ]. However, the molecular mechanism of K + release in exchange for H + in mitochondria is as yet unclear [ 41 ]. With regard to the release pathway of Sr 2+ (Ca 2+ ), K + , and other ions from mitochondria in the oscillatory mode, we suggest that it is mediated by the opening of mitochondrial palmitate/Ca 2+ -induced short-lived lipid pores.…”
Section: Discussionmentioning
confidence: 99%
“…Application of patch-clamp technique also revealed the sensitivity of the mitoK ATP channel to antidiabetic the sulfonylurea—glibenclamide. These properties suggest that in the inner mitochondrial membrane, there are potassium channels similar to the ATP-sensitive potassium (K ATP ) channels present in the plasma membrane of various cells ( Inoue et al, 1991 ; Kravenska et al, 2021 ). Initial observations were focused on the functional characterization of the mitoK ATP channel.…”
Section: Introductionmentioning
confidence: 99%
“…Later, the identification of several other mitochondrial potassium channels such as mitochondrial large-conductance calcium-activated potassium (mitoBK Ca ) channels, mitochondrial intermediate-conductance calcium-activated potassium (mitoIK Ca ) channels, mitochondrial small-conductance calcium-activated potassium (mitoSK Ca ) channels, mitochondrial sodium-activated potassium (mitoSlo2) channels, mitochondrial voltage-regulated potassium (mitoKv) channels and mitochondrial two pore domain potassium (mitoTASK) channels was reported ( Laskowski et al, 2016 ; Krabbendam et al, 2018 ; Kravenska et al, 2021 ). The properties, pharmacology and function of these proteins were discussed in a set of review publications summarized in Table 1 .…”
Section: Introductionmentioning
confidence: 99%